2015
DOI: 10.3109/1547691x.2015.1030804
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of neurodegeneration linked with neuroinflammation in different brain areas of rats after intracerebroventricular colchicine injection

Abstract: Colchicine induces neurodegeneration, but the extent of neurodegeneration in different areas of the brain in relation to neuroinflammation remains unclear. Such information may be useful to allow for the development of a model to compare colchicine-induced neurodegeneration with other neurodegenerative diseases such as Alzheimer's Disease (AD). The present study was designed to investigate the extent of neurodegeneration along with neuroinflammation in different areas of the brain, e.g. frontal cortex, parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Pro-inflammatory cytokines may increase NMDA-induced intracellular Ca 2+ increase by effects on astrocytes, microglia or glutamatergic neurons (Yoshiyama & Groat 2007). Sil et al (2015) reported that ICIR showed increased pro-inflammatory cytokines (TNF and IL-1) levels in different brain areas, indicating neuroinflammation in the brain. Soliven and Albert (1992) reported a dysregulation in Ca 2+ ion influx via NMDA receptor could produce an elevation in intracellular Ca 2+ ions and NO that, in turn, may initiate neuroinflammation in neuronal cells of the superior cervical ganglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-inflammatory cytokines may increase NMDA-induced intracellular Ca 2+ increase by effects on astrocytes, microglia or glutamatergic neurons (Yoshiyama & Groat 2007). Sil et al (2015) reported that ICIR showed increased pro-inflammatory cytokines (TNF and IL-1) levels in different brain areas, indicating neuroinflammation in the brain. Soliven and Albert (1992) reported a dysregulation in Ca 2+ ion influx via NMDA receptor could produce an elevation in intracellular Ca 2+ ions and NO that, in turn, may initiate neuroinflammation in neuronal cells of the superior cervical ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation has been proposed by several investigators as one of the causing factors for neurodegeneration in different chemically-induced animal models of AD, e.g. streptozotocin (STZ), okadaic acid and colchicine when injected intracerebroventricularly (icv) (Nazem et al 2015;Sil et al 2015). Sil et al (2014) reported that neurodegeneration in icv colchicineinjected rats was dependent on cyclooxygenase (COX)-induced neuroinflammation, as naproxen (non-specific COX blocker) could inhibit this neuroinflammation/degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The neuropathology in cAD rats may not be exactly similar to AD as colchicine induces nonspecific neurodegeneration. Intracerebroventricular colchicine injected model of AD rats produced neurodegeneration and amyloid plaques in different parts of the brain which had similarity with the pattern of AD pathology [ 4 ]. The impairment of memory in colchicine induced AD rats also showed similarity with AD patients [ 14 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the axoplasmic flow is blocked, it affects the normal activity of the neurons resulting in its death [ 1 , 2 ]. Intracerebroventricular injection of colchicine in the lateral ventricles of rat causes neurodegeneration in different brain areas including hippocampus and amygdala and as an outcome impairments of cognitive (e.g., memory) [ 3 , 4 ] and noncognitive (e.g., anxiety behavior) functions occur [ 5 ]. Raghavendra et al [ 6 ] have shown that cAD rats exhibit anxiogenic behavior in an elevated plus maze whereas Sil and Ghosh [ 5 ] have reported anxiolytic behavior in cAD rats in an elevated open field with a novel object in the centre along with lower level of serum corticosterone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation